SELF-DISCIPLINE AND A SENSE OF RESPONSIBILITY ARE KEYS TO SUCCESS OF THE UNIVERSITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 15 May 2015 – To ensure the continued excellence of Universiti Sains Malaysia (USM), each member of its community must be selfdisciplined and embody the principles of responsibility and integrity, regardless of whether he or she is being monitored by the head of department or any other party.